PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK DAN PENGETAHUAN AWAL TERHADAP HASIL BELAJAR SENI RUPA KELAS VII DI SMP NEGERI 2 PADANG - EDTRA DELA, Dr. Ramalis Hakim, M.Pd. (Universitas Negeri Padang, 2019)
The purpose of this study is to find out the difference between student learning outcomes taught with a project based learning model with student learning outcomes taught with convetional models of art material. The experimental method at the research site in the state 2 Junior High School. The type of data collected in this study is primary data in the form of the test results of students of Junior High School Negeri number 2 Padang, as the object of research. The results of the study showed that the results of learning the art of Junior High School Negeri number 2 Padang were prepared using the SPSS 16.0 program whithin the application used a project based learning model.